Antiviral effects of probiotic metabolites on COVID-19. Issue 11 (24th July 2021) - Anwar, Firoz; Altayb, Hisham N.; Al-Abbasi, Fahad A.; Al-Malki, Abdulrahman L.; Kamal, Mohammad Amjad; Kumar, Vikas
Abstract: SARS coronavirus (COVID-19) is a real health challenge of the 21st century for scientists, health workers, politicians, and all humans that has severe cause epidemic worldwide. The virus exerts its pathogenic activity through by mechanism and gains the entry via spike proteins (S) and Angiotensin-Converting Enzyme 2 (ACE2) receptor proteins on host cells. The present work is an effort for a computational target to block the residual binding protein (RBP) on spike proteins (S), Angiotensin-Converting Enzyme 2 (ACE2) receptor proteins by probiotics namely Plantaricin BN, Plantaricin JLA-9, Plantaricin W, Plantaricin D along with RNA-dependent RNA polymerase (RdRp). Docking studies were designed in order to obtain the binding energies for Plantaricin metabolites. The binding energies for Plantaricin W were −14.64, −11.1 and −12.68 for polymerase, RBD and ACE2 respectively comparatively very high with other compounds. Plantaricin W, D, and JLA-9 were able to block the residues (THR556, ALA558) surrounding the deep grove catalytic site (VAL557) of RdRp making them more therapeutically active for COVID-19. Molecular dynamics studies further strengthen stability of the complexes of plantaricin w and SARS-CoV-2 RdRp enzyme, RBD of spike protein, and human ACE2 receptor. The present study present multi-way options either by blocking RBD on S proteins or interaction of S protein with ACE2 receptor proteins or inhibiting RdRp to counter any effect of COVID-19 by Plantaricin molecules paving a way that can be useful in the treatment of COVID-19 until some better option will be available. Communicated by Ramaswamy H. Sarma